Effectiveness of Peduli Family Module to Engage Diet, Exercise, and Medication Adherence on Type 2 Diabetes - Trisnadewi, Ni Wayan; Oktaviani, Ni Putu Wiwik; Resiyanthi, Ni Komang Ayu (YCAB Publisher, 2025)
Background:For diabetes patients, adhering to lifelong self-care routines is a significant challenge. Objectives:This study aimed to introduce the PEDULI family module, which can be used as an educational tool for the families of diabetes patients and as a training resource for diabetes educators Methods:This study employed a quasi-experimental design with a pretest-posttest. A total of 82 diabetes patients were involved. PEDULI family module, designed to enhance diabetes management through family involvement. Diet, exercise and medication adherence were measured. Results: The intervention was highly effective in improving diet, exercise, and medication adherence, as well as overall health behavior. Exercise and medication adherence saw particularly strong improvements, influenced by demographic factors such as education, occupation, and family size. Conclusion:These findings suggest that future interventions should consider tailoring strategies to individual characteristics to maximize their effectiveness. Keywords:adherence; diet; exercise; engagement; family; medication